Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.hrthm.2021.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Major adverse clinical events associated with implantation of a leadless intracardiac pacemaker

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 14 publications
2
35
0
Order By: Relevance
“… 4 In a report of the MAUDE database, three episodes of VF/VF were reported, all in the setting of perforation and effusion. 5 …”
Section: Drs Blank and El-chami Commentmentioning
confidence: 99%
“… 4 In a report of the MAUDE database, three episodes of VF/VF were reported, all in the setting of perforation and effusion. 5 …”
Section: Drs Blank and El-chami Commentmentioning
confidence: 99%
“…Subsequent studies suggested that Micra implant success rates were high and the incidence of major adverse clinical events (MACEs) was low 2–6 . Recently, we reported our analysis of MACE associated with Micra‐TPS implantation based on information obtained from the USA Food and Drug Administration (FDA) Manufacturer and User Facility Device Experience (MAUDE) database 7 . While their incidence appeared to be low, we found a concerning number of deaths and other MACE caused by Micra‐TPS cardiac perforations.…”
Section: Introductionmentioning
confidence: 99%
“…The basis of the analyses is principally the Food and Drug Administration (FDA) Manufacturer and User Facility Device Experience (MAUDE) database, but it also includes reports to other FDA databases. The analysis builds on a prior report of safety events related to the Micra® leadless pacing device this time with more than 50% more events 2 . Differences in search strategies are not provided, but the present study reports the use of proprietary software to improve completeness and a slightly larger period of interest (7 months).…”
Section: Introductionmentioning
confidence: 99%